British Steamship Workers, c. 1875–1945: Precarious before Precarity. (May 2019) - Hyslop, Jonathan
Abstract : Much current work on labour conditions is founded on the notion of precarity. This article contends that there is a lack of historical depth in the use of this concept. By looking at the case of British steamship workers, it argues that the Standard Employment Relationship (SER) which precarity theory has attributed to "advanced" economies in the twentieth century was not always the norm. The employment of British steamship workers was never characterised by a SER. They lacked labour freedom and were regularly imprisoned for work-related offences. They were never fully participant in the democratising processes that played out in liberal democratic societies. Seafarers were to an extraordinary extent subject to long-term debt relationships which generated structural poverty. They had life trajectories of a "catastrophic" character, involving difficulty in forming stable families, serious injury and early death. While British steamship workers were relatively privileged in relation to colonised workers, their case nevertheless places a question mark over the standard precarity theory narrative of the rise and fall of the SER.